FUNDAMENTALS OF ENSURING ECONOMIC GROWTH IN THE REGION - Aminov Fazlitdin Baxadirovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article presents the scientific and theoretical definitions given by economists to the concepts of “economic growth” and “economic potential” and their comparative analysis, as well as the importance of regional potential in ensuring sustainable economic development and economic growth. It highlights the main elements of economics growth and the categorization of the economic potential and the possibility of its use. The directions of strategic management are explained.